Ixodid fauna and seasonal dynamics of Hyalomma anatolicum Koch. 1844 population in the Nakhchivan Autonomous Republic - M. A. Seyidov (Российский паразитологический журнал)
The purpose of the research is to study ixodid fauna and the distribution of some species to take timely and effective measures against ticks.Materials and methods. In the Nakhchivan Autonomous Republic, we examined 14,207 domestic animals of 8 species of which 5,512 (38.8%) were found to be infected with ticks. 30,025 specimens of ixodid tick’s imago were collected from the animals. The collected material was examined at the Laboratory of Veterinary Medicine of the Nakhchivan State University and the Laboratory of Parasitology of the Nakhchivan Scientific Center of Veterinary Medicine. The ticks were identified using the identification guide by N. A. Filippova.Results and discussion. The parasitism of 16 species of ixodid ticks of four genera was recorded in the domestic animals in the Nakhchivan Autonomous Republic, namely, Hyalomma, Rhipicephalus, Dermacentor, and Haemaphysalis. Fifteen parasite species were found on the body of the livestock animals, of which 4 species, Hyalomma asiaticum, H. anatolicum, Rhipicephalus bursa, and Dermacentor marginatus were dominants. The H. anatolicum range occupied almost the entire Nakhchivan Autonomous Republic and made up 25.7% of the total and 44.4% of the tick gender collection. H. anatolicum is considered to be the dominant in terms of distribution.